2007
DOI: 10.1074/jbc.m702321200
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Modulates Complement Factor H Expression in Retinal Pigmented Epithelial Cells by Acetylation of FOXO3

Abstract: Age-related macular degeneration (AMD), the leading cause of severe vision loss in the elderly, is a complex disease that results from genetic modifications that increase susceptibility to environmental exposures. Smoking, a major source of oxidative stress, increases the incidence and severity of AMD, and antioxidants slow progression, suggesting that oxidative stress plays a major role. Polymorphisms in the complement factor H (CFH) gene that reduce activity of CFH increase the risk of AMD. In this study we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
82
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(89 citation statements)
references
References 48 publications
5
82
2
Order By: Relevance
“…Recent evidence suggests that oxidative stress downregulates SIRT1 (8,33,34). It is tempting to postulate that the ongoing reactive oxygen species generation by ethanol metabolism could prolong the suppression of SIRT1 activity in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that oxidative stress downregulates SIRT1 (8,33,34). It is tempting to postulate that the ongoing reactive oxygen species generation by ethanol metabolism could prolong the suppression of SIRT1 activity in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Synovial cells are now stressed and susceptible to complement-induced injury, further increasing the requirement for fH control of AP activation. Notably, this same role for fH in regulation of inflammation is observed in ischemic injury in renal tubular epithelial cells (41) and in oxidative stress in retinal pigmented epithelial cells (42) fH is increasingly recognized as a centrally important protein in the regulation and control of AP activation on multiple tissue sites. The normal concentration of fH in plasma ranges from 233 to 269 mg/ml in young and old individuals, respectively (43), although other studies suggest that the concentration of fH in plasma is 2-fold higher (44,45).…”
Section: Discussionmentioning
confidence: 72%
“…However, in certain CNS pathologies such as multiple sclerosis (Ingram et al , 2010 ), there is a reported increase in AMBP-1 levels. Infl ammatory cytokines, particularly IFN-γ , have been recognized as positive regulators of AMBP-1 expression (Wu et al , 2007b ), whereas Cerebral ischemia results in infl ammation and production of reactive oxygen species. Reactive oxygen species (ROS) causes acetylation (Ac) of FOXO3, which translocates into the nucleus and binds to the AMBP-1 promoter, followed by suppression of AMBP-1 expression.…”
Section: Alterations In Ambp-1 Levels In Brain Diseasesmentioning
confidence: 99%
“…The balance between negative and positive regulators will determine whether AMBP-1 level in brain disease is up-or down-regulated. Wu et al (2007b) demonstrated that during infl ammation, IFN-γ stimulates the nuclear translocation of STAT1 together with relatively small amount of FOXO3 to bind to the STAT1 response element in the AMBP-1 promoter region, leading to up-regulation of AMBP-1 expression. However, in the presence of reactive oxygen species, FOXO3 undergoes a conformational change by acetylation.…”
Section: Alterations In Ambp-1 Levels In Brain Diseasesmentioning
confidence: 99%